How Many Wild Edible Plants Do We Eat—Their Diversity, Use, and Implications for Sustainable Food System: An Exploratory Analysis in India - Ray, Avik; Ray, Rajasri; Sreevidya, E. A. (Frontiers in Sustainable Food Systems, 2020)
Wild edible plants still cater to a large section of the global population and ensure affordable food and nutritional security. We tested this in an Indian context, where enormous diversity of such plants constitutes a significant part of rural diet and their acceptance has been high. In this study, we assessed diversity of wild edible plant resource, importance of species based on the use and its pattern. We have also shortlisted a set of plants to make an informed-decision on prioritization. We found a great variety of plants (1403 species) from 184 families consumed across India, although the first forty-four families (24%) contributed largely to the (75%) diversity. Leguminosae followed by Compositae, Poaceae, Malvaceae, Rosaceae were the families with highest number of species. We note that a few species from the large pool were extensively used throughout the country while another few were valued for their multiple edible plant parts. Leafy shoots (722 species) followed by fruits (652 species) were two most-eaten plant parts. Our results strengthen the fact that (a) wild edibles have been an integral part of the diet, (b) their widespread assimilation into local food culture suggests untapped potential to ensure easy availability and access to micronutrients for sustainable food system, thus in social welfare, (c) they required to be incorporated into the national food policy for formal cultivation and promotion.